(untitled) (Bangladesh Journal of Animal Science, 2012)
Fifteen castrated male goats (12.97±1.46 Kg) aged between 12 and 13 months were used to study the effect of different levels of concentrate supplementation on growth performance and nutrient digestibility in Black Bengal goat under stall feeding. The feeding trial was continued for a period of 75 days where goats were supplied at the rate of 158g DM/kgW.75 /day. The animals were assigned into five dietary treatments: A (Only dal grass as sole feed), B (15% DM from concentrate + 85% DM from dal grass), C (20% DM from concentrate +80% DM from dal grass), D (25% DM from concentrate + 75% DM from dal grass), E (30% DM from concentrate + 70% DM from dal grass). Digestibility of all nutrients was gradually higher (P<0.01) from A to E. Total live weight gain of goats of group A was statistically lowest (P<0.01) than those of other groups. There was also significant difference (P<0.01) among the treatment groups E, D, C and B. Live weight was gradually increase due to gradual increase of concentrate from B to E. Nitrogen balance, carcass yield and net profit of treatment group E was highest (P<0.01) then D, C and B than A. Green grass do not fulfill the appetite and nutrient requirements as a sole feed. Concentrate supplementation is undoubtedly essential to fulfill the nutrient requirements and concentrate can be supplemented upto 30% of required DM to obtain the best result. DOI: http://dx.doi.org/10.3329/bjas.v40i1-2.10789 Bang. J. Anim. Sci. 2011. 40 (1-2): 40-45